Genome‐wide association study and identification of chromosomal enhancer maps in multiple brain regions related to autism spectrum disorder. Issue 1 (29th August 2018) - Zhang, Lu; Liu, Li; Wen, Yan; Ma, Mei; Cheng, Shiqiang; Yang, Jian; Li, Ping; Cheng, Bolun; Du, Yanan; Liang, Xiao; Zhao, Yan; Ding, Miao; et al.
Abstract : Autism spectrum disorder (ASD) is a complex developmental disorder with strong genetic components involved. Recent studies have demonstrated the importance of non‐coding regulatory variants for complex diseases. To explore the roles of chromosomal enhancer regions in the pathogenesis of ASD, we conducted an integrative analysis of genome‐wide association study (GWAS) and brain region related enhancer‐gene networks for ASD. The GWAS data of ASD were driven from a published study, involving 7, 387 ASD cases and 8, 567 controls. The enhancer‐gene networks of eight brain regions were used here. The GWAS of ASD was first merged respectively with the enhancer datasets of eight brain regions. Pathway enrichment analysis was then performed to detect ASD associated pathways based on the enhancer‐related single nucleotide polymorphism (SNPs) of each brain region. We detected multiple genes with brain region specific or common association signals, such as PGM3 ( P value = 1.93 × 10 −5 ) and RWDD2A ( P value = 1.93 × 10 −5 ) for hippocampus middle, and ENPP4 (all P values <0.05), and ENPP5 (all P values <0.05) for seven brain regions. By comparing the pathway enrichment analysis results of various brain regions, several cross brain regions pathways were detected for ASD, such as REACTOME_POTASSIUM_CHANNELS (all P values <0.05) for six brain regions and KEGG_CELL_ADHESION_MOLECULES_CAMS (all P values <0.05) for seven brain regions. In addition, several pathways were also identified for specific brain regions, such as REACTOME_CD28_DEPENDENT_PI3K_AKT_SIGNALING ( P value = 4.00 × 10 −3 ) for angular gyrus, REACTOME_SIGNALING_BY_CONSTITUTIVELY_ACTIVE_EGFR ( P value = 2.22 × 10 −3 ) for anterior caudate, and KEGG_PRION_DISEASES ( P value = 1.00 × 10 −4 ) for germinal matrix. Our results provide novel clues for understanding the genetic basis of ASD. Autism Research 2019, 12: 26–32 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: ASD is a complex developmental disorder with strong genetic components, but the pathogenesis of ASD is still unclear. Using the latest GWAS data and enhancer map, we explored the brain region related biological pathways associated with ASD. Our results provide novel clues for revealing the functional relevance of enhancer variants with ASD and understanding the genetic basis of ASD.